Study of a palm slag-filled friction composite for brake pad - Che Mohd Ruzaidi, Ghazali
Since the use of asbestos was banned in all types of products and applications due to its carcinogenic nature, researchers worldwide has conducted extensive research and development activities with the goal of identifying alternative and safe materials. This research work was conducted with the main objective of determining the potential and capability of using palm slag, an industrial solid waste that is abundant in Malaysia, as an alternative filler material in friction composites for brake pad applications. The other main ingredient that were used to develop friction composites in this research were, phenolic resin as a binder, graphite as a lubricant, alumina as an abrasive and steel fibers to provide reinforcement. The mixture was hand press compacted to have the 10 mm diameter cylindrical green body before being further compacted and cured in a hot press at the 160 oC for five (5) minutes. Then the samples were post-cured in the oven at 160 oC for four (4) hours before being tested for hardness, density, compressive strength and resistance to wear. Characterization of the raw material, especially the thermal behaviour of the palm slag, showed that it was thermally stable and suitable for use as the filler material in brake pads. The processing parameters with higher molding pressures had significant effects on the brake pad’s end properties, such as density, hardness and compressive strength of the friction composite. The result of this study also indicated that the mechanical properties of the composite material were inversely related to the size of the palm slag particles that comprise the composite. The wear rate of the friction composite was influenced by the type of filler, moulding pressures and particle size of the filler. As a conclusion, this study was determined that, palm slag could be one of the alternative fillers used in brake pad with a comparable © This item is protected by original copyright xix wear properties to the commercial brake pad products in the market. It was also found that, after a certain initial period of use, the trend of wear rate for various sliding distances was essentially constant and linear. Lastly, on road brake test was recommended to be performed for further study in the future to validate the formulation or a real application in the vehicle.